ANTIMICROBIAL RESISTANCE AND CLINICAL OUTCOMES OF BLOODSTREAM INFECTIONS IN A CARDIOVASCULAR SURGERY DEPARTMENT - Tayfun Özdem; Mehmet Emin Varol; Ali Can Korkmaz; Ilgaz Kazaz; Tuna Demirkıran; Işil Taşöz; Furkan Burak Akyol; Ertan Demirdaş; Gökhan Erol; Tuğrul Hoşbul; Hakan Kartal (Karya Journal of Health Science, 2026)
Objective: Bloodstream infections (BSIs) following cardiovascular surgery and cardiovascular interventions are major postoperative complications associated with substantial morbidity and mortality. Although antimicrobial resistance (AMR) has become an increasingly important global public health concern, this study aimed to clarify its impact on clinical outcomes in patients who develop postoperative BSIs.Method: This retrospective study included 139 adult patients who developed BSIs after cardiovascular surgery or cardiovascular interventions at a tertiary referral center. The associations of multidrug resistance (MDR), carbapenem resistance (CR), methicillin resistance, and penicillin resistance with mortality, hospital length of stay (LOS), intensive care unit (ICU) stay, and mechanical ventilation duration were evaluated. Independent predictors of mortality were identified using multivariable logistic regression analysis.Results: The overall mortality rate was 30.9%. Gram-negative pathogens accounted for 56.8% of BSIs and Gram-positive pathogens for 43.2%. Staphylococcus species were the most frequently isolated pathogens (33.8%), comprising other Staphylococcus species (26.6%) and Staphylococcus aureus (7.2%), followed by Klebsiella pneumoniae (21.6%) and Acinetobacter baumannii (12.9%). Neither MDR nor CR was significantly associated with mortality (p>0.05). However, among patients with Gram-negative BSIs, carbapenem-resistant isolates were associated with significantly longer hospital, and ICU stays than carbapenem-susceptible isolates (both p=0.006). Univariable analyses showed significant associations between mortality and Gram-negative BSIs, diabetes mellitus, hypertension, and surgical procedure type. Multivariable analysis identified prolonged cardiopulmonary bypass (CPB) duration (OR=1.015, 95% CI: 1.005–1.025; p=0.003) and Gram-negative BSI (OR=3.938, 95% CI: 1.225–12.659; p=0.021) as independent predictors of mortality.Conclusion: AMR was associated with greater healthcare resource utilization, particularly prolonged hospital and ICU stays, but was not significantly associated with mortality in this cohort. In contrast, Gram-negative BSIs and prolonged CPB duration were independent predictors of mortality.